2003
DOI: 10.1119/1.1616479
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Measurement in the Introductory Physics Laboratory

Abstract: Traditionally physics laboratory courses at the freshman level have aimed to demonstrate various principles of physics introduced in lectures. Experiments tend to be quantitative in nature with experimental and data analysis techniques interwoven as distinct strands of the laboratory course.1 It is often assumed that, in this way, students will end up with an understanding of the nature of measurement and experimentation. Recent research studies have, however, questioned this assumption.2,3 They have pointed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 8 publications
0
30
0
3
Order By: Relevance
“…Some laboratories have introduced new educational technologies (e.g., microcomputer-based labs [7] and VPython [8,9]), others have added an emphasis on particular scientific practices (e.g., measurement and uncertainty [10,11], developing testable questions and designing experiments [12,13], and scientific argumentation [14]), while others have pushed the lab course closer to cuttingedge research by introducing modern physics concepts and apparatus (e.g., single photon quantum optics experiments [15,16]), and others have demonstrated improved conceptual learning gains through research-based lab activities [17]. The diversity of responses reflects both the diversity of goals for the laboratory and the flexibility and adaptability of the laboratory environment to meet many different goals.…”
Section: Introductionmentioning
confidence: 99%
“…Some laboratories have introduced new educational technologies (e.g., microcomputer-based labs [7] and VPython [8,9]), others have added an emphasis on particular scientific practices (e.g., measurement and uncertainty [10,11], developing testable questions and designing experiments [12,13], and scientific argumentation [14]), while others have pushed the lab course closer to cuttingedge research by introducing modern physics concepts and apparatus (e.g., single photon quantum optics experiments [15,16]), and others have demonstrated improved conceptual learning gains through research-based lab activities [17]. The diversity of responses reflects both the diversity of goals for the laboratory and the flexibility and adaptability of the laboratory environment to meet many different goals.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentation and measurement lie at the heart of physics, and it is important that students develop an understanding of these concepts. 14 However, the goal of measurement is often seen by these students almost exclusively acquiring a single "point" value for the quantity they are investigating, 15 and not also realizing that there is measurement error and other aspects of variability which creates uncertainty in the point estimate. Lying at the heart of the problem is the great difficulty students have in translating the "words" of a problem into a "picture" of reality, where physical objects relate to each other through physical laws.…”
Section: Introductionmentioning
confidence: 99%
“…14,17 Yet conducting proper analysis of experimental uncertainty is a primary goal of introductory physics labs. 13 Previous studies 18,19 found that students leave introductory physics laboratory courses with an ability to carry out certain procedures, but lack a coherent understanding for the nature of uncertainty, irrespective of the student profile, or the way in which the laboratory course was delivered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halfway through the second semester of the course, students worked in pairs or groups of three to determine the index of refraction (n) of a plexiglass prism through the application of Snell's Law, the critical angle for Total Internal Reflection, and Brewster's Angle. The students had received instruction earlier in the year on assessing whether measurements were in agreement and on quantifying uncertainties from digital and analog scales and due to statistical fluctuations [7].…”
Section: The Lab: Index Of Refractionmentioning
confidence: 99%